The diversity of a snake community in a karst forest ecosystem in the central Truong Son, Vietnam, with an identification key - Ziegler, Thomas; Hendrix, Ralf; Thanh, Vu Ngoc; Vogt, Martina; Forster, Bernhard; Kien, Dang Ngoc (Zootaxa, 2007)
A review of the snake diversity of Phong Nha Ke Bang, central Truong Son, Vietnam is given. As the result of recent field work, we add nine species to the region’s karst forest snake fauna: Amphiesma sp., Calamaria thanhi, Gonyosoma prasinum, Liopeltis frenatus, Lycodon cf. ruhstrati, Lycodon sp., Pareas hamptoni, P. macularius, and Pseudoxenodon macrops. The evidence of Calamaria thanhi from within the Phong Nha Ke Bang National Park’s borders in addition represents the second finding of this recently described and barely known species as well as the first male recorded. A topical list of the 59 snake species recorded from the area is presented (two Typhlopidae, two Xenopeltidae, two Pythonidae, five Elapidae, five Crotalidae, and 43 colubrid snakes) and compared with the snake fauna known from Tam Dao mountain ridge in northern Vietnam. Species being expected in the future to be recorded within the Phong Nha Ke Bang region are introduced and zoogeographical aspects of the regional snake’s fauna composition are discussed. Besides an overview of the spatial and temporal niche segregation of the Phong Nha Ke Bang snake community we show the snake species abundances based on own field surveys in the period between 1998 and 2006. Finally, we provide an identification key to the snake species recorded from Phong Nha Ke Bang and adjacent provinces in central Vietnam.